Analysis of Factors Affecting Net Profit Margin: A Study of Telecommunication Companies - Palevi Alren, Reza; Nurwati, Etty; Purwanto, Sri; Moeljadi; Supriadi, Yudi Nur; Mulyantini, Sri (Yayasan Sinergi Kawula Muda, 2026)
This study investigates the impact of Return on Equity (ROE), Equity Ratio (ER), and Asset Turnover Ratio (ATR) on Net Profit Margin (NPM) among telecommunication companies listed on the Indonesia Stock Exchange during 2018–2022. Employing a quantitative approach with panel data regression using the Random Effects Model and secondary data from company annual reports, the findings indicate that ROE exerts a positive but relatively weak influence on NPM, while ER demonstrates a positive relationship approaching significance. Conversely, ATR shows a significant negative effect, underscoring that asset efficiency contributes less to profitability in the capital-intensive telecommunications sector. The model achieves an adjusted R² of 0.874, suggesting strong explanatory power. Overall, the results emphasize that managerial strategies should prioritize optimizing equity utilization and maintaining a robust capital structure rather than relying on asset turnover efficiency. Despite being limited to five firms and secondary data, this research enriches sector-specific financial performance analysis and provides valuable insights for managers and policymakers. Future studies are encouraged to extend the model by incorporating factors such as technological innovation, market competition, and regulatory dynamics to capture a more comprehensive understanding of profitability determinants in the industry.